Sensorineural Deafness Among Patients with Chronic Renal Failure in Al-kindi Teaching Hospital - Aloubaide, Raad Aboud; Alsaedi, Ali Jassim; Saker, Raed; Jamil, Nawar Satta; Mohammed, Faris Abbass (AL-Kindy College Medical Journal, 2011)
Background: Patients with chronic kidney disease have different grades of sensorineural deafness . Objective: To study the incidence of sensorineural hearing loss and possible contributing factors in patients with chronic kidney disease. Methods: A total of 100 patients with chronic kidney disease were studied. All of them were males. 92 of them were on regular haemodialysis programme. Only 8 patients were on conservative management the age range of the study patients was 18-40 year patients were divided into three groups according to age. All patients were assessed clinically and were evaluated by audiometry , and analysis was made on bone conduction threshold .The mean follow up period was 28 weeks . Results: 36 patients (36 %) showed sensorineural hearing loss .The incidence of sensorineural deafness was found to increase with the advancing age and duration of chronic kidney disease but not directly proportional to the number of haemodialysis sessions .The number of haemodialysis sessions did not show increase in the degree of sensorineural deafness . Conclusion: Patients with chronic kidney disease have sensorineural deafness of some degree which should be assessed and evaluated to halt its progression.